Example for the analysis of a series of experiments arranged in balanced complete blocks - Ávila-Granados, Francisco Antonio; Pérez-López, Delfina de Jesús; Rubí-Arriaga, Martín; Hernández-Ávila, Jesús; Flores-Carrera, Laura Stephanie; González-Huerta, Andrés (Revista Mexicana de Ciencias Agrícolas, 2025)
There is little published information in some series of experiments, such as in the randomized complete block design in a balanced complete block arrangement (RCBD-BCBA). This study presents a hypothetical example to apply the methodology published in González et al. (2024b), which is an extension of a case formulated by Gomez and Gomez (1984). The analysis of variance and the comparison of means between treatments using Fisher’s least significant difference test correspond to the analysis of the data combining the information of two trials, based on the statistical model that was chosen for the present research, the validation of the results generated can be done with other statistical packages, such as Info-Gen, SAS, OPSTAT, STAR, PBTools, or Agrobase, among others.